1993
DOI: 10.1177/00220345930720090701
|View full text |Cite
|
Sign up to set email alerts
|

Acute Toxicological Effects of Ingested Tooth Whiteners in Female Rats

Abstract: Tooth whiteners are considered as cosmetic agents to be used for bleaching teeth. Since tooth whitener may be swallowed during the whitening procedure, studies were conducted to determine whether ingestion of tooth whitener containing carbamide peroxide resulted in toxic effects. Adult female rats were used, and vaginal smears were examined daily to determine whether the animals were ovulating. Following an overnight fast, a single bolus of a commercial tooth whitener (5 g of tooth whitener/kg fasting body wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…For hydrogen peroxide, the oral LD 50 value was found to be approximately 1600 mg/kg (Ito et al, 1976), but no other studies have confirmed the above findings. In rats, a single oral dose of 5 g/kg BW of proprietary solutions of 10%, 15%, and 35% carbamide peroxide induced a concentration-dependent acute toxicity, and the rats showed respiratory depression, reduced weight gain and water consumption, changes in estrous cycle, and, at necropsy, histological abnormalities of the stomach, including necrotic mucosa and disrupted gastric glands (Cherry et al, 1993). In the highest-concentration group, 3 animals died of gastric hemorrhage and bloating.…”
Section: Animal Studiesmentioning
confidence: 99%
“…For hydrogen peroxide, the oral LD 50 value was found to be approximately 1600 mg/kg (Ito et al, 1976), but no other studies have confirmed the above findings. In rats, a single oral dose of 5 g/kg BW of proprietary solutions of 10%, 15%, and 35% carbamide peroxide induced a concentration-dependent acute toxicity, and the rats showed respiratory depression, reduced weight gain and water consumption, changes in estrous cycle, and, at necropsy, histological abnormalities of the stomach, including necrotic mucosa and disrupted gastric glands (Cherry et al, 1993). In the highest-concentration group, 3 animals died of gastric hemorrhage and bloating.…”
Section: Animal Studiesmentioning
confidence: 99%
“…Many of the systems available today use 10, 15–16 or 35% carbamide peroxide as the active bleaching agent ( Yarborough, 1991; Cherry et al , 1993 ). Vital bleaching using carbamide peroxide has been suggested as a safe alternative to vital bleaching with hydrogen peroxide ( Haywood & Heymann, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…8 Animal models can also be used to characterize the toxic effects of bleaching substances. 24 These studies show the genotoxic effect caused by oxidative stress to the DNA, due to the action of peroxide, but the effects are smaller than those found in in vitro studies. This is probably related to the quick detoxification of H 2 0 2 and the elimination of free radicals before any interaction with the DNA.…”
Section: Discussionmentioning
confidence: 93%